1992
DOI: 10.1038/358171a0
|View full text |Cite
|
Sign up to set email alerts
|

Protein images obtained by STM, AFM and TEM

Abstract: Scanning tunnelling microscopy and atomic force microscopy, one scanning the tunnelling current and the other the repulsive atomic force between same and probe, can give high-quality surface topographies of proteins, which have been difficult to obtain by more conventional methods such as transmission electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 17 publications
2
45
0
1
Order By: Relevance
“…Since AFM is able to image the atomic organization of both conductive and nonconductive material, it has is seen as a promising tool for biological studies (for reviews see Lal & John, 1994). A considerable number of investigators have therefore applied AFM to the observation of organic monolayers and bilayers Weisenhorn et al, 1990;Singh & Keller, 1991), ribonucleic and deoxyribonucleic acid (Thundat et al, 1992(Thundat et al, , 1993Hansma et al, 1992Hansma et al, , 1993bYang et al, 1992), amino acid crystals and proteins (Gould et al, 1988;Drake et al, 1989;Arakawa et al, 1992). There are also several reports on AFM observation of viruses, phages and in vitro cells (Butt et al, 1990;Gould et al, 1990;Henderson et al, 1992;Ikai et al, 1993;Kasas et al, 1993;Parpura et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AFM is able to image the atomic organization of both conductive and nonconductive material, it has is seen as a promising tool for biological studies (for reviews see Lal & John, 1994). A considerable number of investigators have therefore applied AFM to the observation of organic monolayers and bilayers Weisenhorn et al, 1990;Singh & Keller, 1991), ribonucleic and deoxyribonucleic acid (Thundat et al, 1992(Thundat et al, , 1993Hansma et al, 1992Hansma et al, , 1993bYang et al, 1992), amino acid crystals and proteins (Gould et al, 1988;Drake et al, 1989;Arakawa et al, 1992). There are also several reports on AFM observation of viruses, phages and in vitro cells (Butt et al, 1990;Gould et al, 1990;Henderson et al, 1992;Ikai et al, 1993;Kasas et al, 1993;Parpura et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Biological membranes containing phospholipid mono-, bi-and multilayers (Zasadzinski et al, 1991), individual reconstituted proteins, e.g. fibrinogen (Wigren et al, 1991), immunoglobulins Ill et al, 1993), phosphorylase kinase complexes (Edstrom et al, 1990) and alpha-macroglobulin (Arakawa et al, 1992) as well as protein arrays in lipid membranes have also been investigated (Arnsdorf & Lal, 1992;Meyerllse et al, 1992;Schabert et al, 1995) with AFM. We performed a pilot study to test the ultramicrography technique described above to obtain high-resolution images of live whole cells of E. coli and of the macromolecules lipopolysaccharide (LPS) and DNA.…”
Section: Introductionmentioning
confidence: 99%
“…These include the fast replication of specific DNA chains (10)(11)(12), the stretching and fixation of such chains on suitably prepared substrates (13), and STM imaging. In particular, the ability to track by STM certain long polymer molecules and to identify their termination has been demonstrated (14).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In this context transmission electron-and atomic force microscopy (TEM and AFM) are frequently used in parallel for the visual characterization of biological molecules (Arakawa et al, 1992;Lin & Goh, 2002). It has been reported that the DNA complexation with chitosans might result in a blend of structures: toroids, rods, and globules, with the relative amounts of the different structures apparently depending on the actual chitosan, the charge ratio, and solution properties like pH and ionic strength (Danielsen et al, 2004;Maurstad et al 2007).…”
Section: Structural Organizationmentioning
confidence: 99%